Applications of Trichoderma formulations in crop protection - Monte E; Rodriguez A; Rey M; Azpilicueta A; Gómez M I; de la Vin a G; Grondona I; Llobelt A (浙江大学学报. 农业与生命科学版)
The choice of active Trichoderma strains is important in designing effective and safe biocontrol applications. Many species of Trichoderma have multiple strategies for fungal antagonism and indirect effects on plant health, such as growth promotion, systemic resistance induction and fertility improvements. Some strains are powerful antibiotic producers, and their suitability for use in biocontrol systems must be carefully assessed. However, many other active strains have no antibiotic capacity, and these are likely to be more useful in food production systems since they have not adverse effects on important groups of beneficial soil organisms. We have assessed the performance of selected naturally occurring Trichoderma strains (singly and in combination) and developed TUSAL®, a mixture of Trichoderma harzianum and T. viride that has demonstrated to be effective against major pathogens in sugar beet and horticulture. TUSAL®, has been bulked up and tested under field conditions, showing positive effects on precocity and root development, and increasing the crop production in field trials carried out in different pathosystems. The environmental impact of TUSAL® strains on beneficial organisms in the environment were assessed before release, and molecular detection methods were developed to monitor the presence and performance of strains in the field.In addition, Trichoderma protein extracts with high glucanase and chitinase activities, have also been obtained from wild type strains and their effectiveness as biofungicides was tested in laboratory and field conditions, defining the concentration of protein necessary to produce fungicide effects. The genes coding for protein production were introduced into suitable organisms for large-scale production in the laboratory, never released to the environment. The effect of these novel biofungicide proteins was studied separately and synergistically with Trichoderma conidia, and with minimal doses of chemical fungicides. Suitable active Trichoderma strains are being registered in the EU by the company NBT. Both Trichoderma strains and proteins are included in formulations patented as biocontrol agents.